Interior MARSitecture: Contributing to Psychological Wellbeing Through the Development of Recommendations for the Interior Design of Habitats in Isolated, Confined and Extreme Environments - Lane, Jennifer Ashley (Curtin University, 2025)
Interior MARSitecture aims to understand how the interior design of habitats can contribute to the psychological wellbeing of astronauts who will one day inhabit Mars. Findings are presented from analysis of the experiences of people who have lived in environments considered analogues to Mars (including Antarctic stations, the International Space Station and Mars Simulations). Data was gathered through interviews, a questionnaire, and researcher autoethnography to make recommendations on the interior design of future habitat.